PENGARUH PEMBERIAN KOMBINASI NAC DENGAN VITAMIN C DAN E TERHADAP STRES OKSIDATIF PADA HUVECs DIPAPAR PLASMA EKLAMPSIA - Baktiyani, Siti Candra Windu (Jurnal Kedokteran Brawijaya, 2007)
The blood plasma of preeclampsia contains oxidative stress factors. The oxidative stress is predicted asthe cause of dis-function and destruction of endothelial cell which will influence the severity of Preeclampsia and Eclampsia complications. Previous research showed that the treatment of antioxidant on preeclamsia was still controvertion. The  objectives of this research is to investigate the influence of the combination of NAC and vitamin C or vitamin E or bothof them on the level of H2O2, MDA, NO and GSH/GSSG ratio of endothelial cell culture exposed with Eclampsia plasma.The method wasan experimental study using HUVECs exposed with to 2%plasma Eclampsia as an Eclampsia model invitro. TheHUVECs were than treated with NAC 2µM only (group 1), NAC2µM + vitamin C 100 µM (group 2) , NAC 2 µM + vitamin E 100 µM (group 3), and NAC 2 µM + vitamin C 100 µM + vitamin E 100 µM (group 4) for 24 hours. The parameter measured in this study were H2O2, MDA, NO and GSH/GSSG ratio. Result showed that H2O2, MDA, and NO concentration are unsignificantly different among treatment groups although there was a decreasing on group treated with combination of NAC, vitamin C and Vitamin E.